EDITORIAL - Vargas, J. V. C. (Revista de Engenharia Térmica, 2012)
Around the end of the twentieth century, nanotechnology appeared to be the new breakthrough, after the internet, for example. At that time, more efficient and affordable solar cells, green chemistry, quantum computing, lightweight composite aircraft, cell-size robots for medical applications were expected to be available soon. When the financial milestones did not become real, investors got disappointed and decided to rethink their plans. Yet today the perspectives are surprisingly upbeat. Currently, it is well known that restructuring matter at the nanoscale chemical and thermophysical properties change, so that systems that have no purpose at the macroscale, at the nanoscale become useful. In fact, several applications have already begun to appear such as in the oil and gas sector components, structured coatings, nanofluids, new cancer treatment drugs, and nanoviricides. Computer processor and memory manufacturers are already producing products with 32 nanometer components, so that the first commercial memristor (memory resistor) is expected to be launched at the end of 2013. In the renewable energy area, just to cite a few examples, low energy consumption nanostructured inexpensive LEDs are being developed to potentially last for years, carbon nanotubes have been used to drastically reduce precious materials content in proton-exchange fuel cell (PEMFC) electrodes and increase efficiency, and nanostructured thin films are being developed to boost photovoltaic performance and reduce costs, which demonstrated a 23.5 % efficient flexible solar panel operating a 2 MW pilot line at the National Renewable Energy Laboratory in the US. In comparison to market available 10 % efficient solar panels, this is a remarkable efficiency increase in capturing solar energy for practical use due to nanotechnology. This nanotechnological achievement challenges scientists to possibly change the currently fuel (fossil and bio) energy driven world into a solar energy driven one.